Systematics of the parasitoid wasp genus Aulacus Jurine (Hymenoptera: Evanioidea: Aulacidae) from Australia - Jennings, John T.; Parslow, Ben A.; Austin, Andrew D. (Zootaxa, 2018)
The Aulacidae is a small family of Hymenoptera that are parasitic on wood-boring beetles and wasps. They have a worldwide distribution but are generally poorly studied, particularly for the southern hemisphere. This study is part of a series that aims to describe the Australian fauna which is relatively species-rich compared with other regions. We describe 39 new Aulacus species from eastern mainland Australia and Tasmania: A. anici Jennings & Austin, sp. nov., A. aquilus Jennings & Austin, sp. nov., A. bamagensis Jennings & Austin, sp. nov., A. bashfordi Jennings & Austin, sp. nov., A. bicolor Jennings & Austin, sp. nov., A. boonanghiensis Jennings & Parslow, sp. nov., A. brabyi Jennings & Austin, sp. nov., A. broadi Jennings & Austin, sp. nov., A. burnsi Jennings & Austin, sp. nov., A. confusus Jennings & Parslow, sp. nov., A. dandenongensis Jennings & Austin, sp. nov., A. deansi Jennings & Austin, sp. nov., A. doddi Jennings & Austin, sp. nov., A. froggatti Jennings & Austin, sp. nov., A. glorious Jennings & Parslow, sp. nov., A. hackeri Jennings & Austin, sp. nov., A. insularis Jennings & Austin, sp. nov., A. jamberoo Jennings & Parslow, sp. nov., A. kittelae Jennings & Austin, sp. nov., A. kiwarrakensis Jennings & Austin, sp. nov., A. leai Jennings & Austin, sp. nov., A. mareebaensis Jennings & Austin, sp. nov., A. naumanni Jennings & Austin, sp. nov., A. nebo Jennings & Austin, sp. nov., A. neboissi Jennings & Austin, sp. nov., A. obcordellus Jennings & Parslow, sp. nov., A. pallidus Jennings & Austin, sp. nov., A. quickei Jennings & Austin, sp. nov., A. rieki Jennings & Austin, sp. nov., A. scitulus Jennings & Parslow, sp. nov., A. simsoni Jennings & Austin, sp. nov., A. smithi Jennings & Austin, sp. nov., A. tasmanicus Jennings & Austin, sp. nov., A. tiernyi Jennings & Austin, sp. nov., A. umbackae Jennings & Austin, sp. nov., A. walkeri Jennings & Parslow, sp. nov., A. warraensis Jennings & Austin, sp. nov., A. willamsi Jennings & Austin, sp. nov., and A. wrightae Jennings & Austin, sp. nov. We also redescribe 14 species: A. albimanus (Kieffer), A. aroueti (Girault), A. atriceps Kieffer, A. elegans (Kieffer), A. festivus (Kieffer), A. flavicornis (Kieffer), A. flavimanus (Kieffer), A. fuscicornis Cameron, A. longiventris (Kieffer), A. minutus Crosskey, A. pallidicaudis (Cameron), A. planiceps (Szépligeti), A. truncatus (Kieffer), and A. vespiformis (Kieffer). As well, A. nigriventris (Kieffer) is synonymised with A. albimanus (Kieffer) syn nov. This brings to 60 the total number of species known from Australia (71 for the Australian region), although one species, A. biroi (Szépligeti), remains incertae sedis. A key to Australian Aulacus species is presented, along with notes on taxonomic history and host relationships.